2020
DOI: 10.1101/2020.08.22.262733
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lipid droplets fuel SARS-CoV-2 replication and production of inflammatory mediators

Abstract: Viruses are obligate intracellular parasites that make use of the host metabolic machineries to meet their biosynthetic needs, identifying the host pathways essential for the virus replication may lead to potential targets for therapeutic intervention. The mechanisms and pathways explored by SARS-CoV-2 to support its replication within host cells are not fully known. Lipid droplets (LD) are organelles with major functions in lipid metabolism and energy homeostasis, and have multiple roles in infections and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
(65 reference statements)
4
13
0
Order By: Relevance
“…First, we report here that monocytes treated with recombinant spike protein subunit 1 from the current pandemic SARS-CoV-2 undergo a dose-dependent increase in glycolysis which is controlled by HIF-1α and mediates the production of pro-inflammatory cytokines. These data suggest an initial signaling event which precipitates changes in glucose and lipid metabolism during SARS-CoV-2 infection in monocytes which have been previously reported to be linked to inflammatory activation 34,35 . Monocyte and monocyte-derived macrophages are substantially enriched in the lungs of SARS-CoV-2-infected individuals with severe COVID-19 8,9,1215 and respond to experimental viral infection by producing pro-inflammatory cytokines 3438 , therefore these results reflect a potential mechanism by which hypercytokinemia occurs during the early innate immune response to SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…First, we report here that monocytes treated with recombinant spike protein subunit 1 from the current pandemic SARS-CoV-2 undergo a dose-dependent increase in glycolysis which is controlled by HIF-1α and mediates the production of pro-inflammatory cytokines. These data suggest an initial signaling event which precipitates changes in glucose and lipid metabolism during SARS-CoV-2 infection in monocytes which have been previously reported to be linked to inflammatory activation 34,35 . Monocyte and monocyte-derived macrophages are substantially enriched in the lungs of SARS-CoV-2-infected individuals with severe COVID-19 8,9,1215 and respond to experimental viral infection by producing pro-inflammatory cytokines 3438 , therefore these results reflect a potential mechanism by which hypercytokinemia occurs during the early innate immune response to SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 60%
“…Recently it was demonstrated that SARS-CoV-2 promotes metabolic reprogramming in monocytes during infection 34,35 . Research in SARS-CoV suggested that the viral spike protein induces inflammatory responses in macrophages 40,41 , and this has recently been replicated using spike protein from SARS-CoV-2 42,43 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it was reported that HMG-CoA reductase is necessary to produce lipid droplets (LD) [39]. These cell organelles have been recently proposed as hubs for SARS-CoV-2 genome replication and viral particle assembly [40, 41]. According to the above, ATV treatment could affect the replication and assembly stages of SARS-CoV-2 by blocking LD production.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of viral protein associated with proteins linked with LDs has also been studied in numerous positive-strand RNA viruses (Cheung et al 2010;Coffey et al 2006;Filipe and McLauchlan 2015;Lyn et al 2013;Samsa et al 2009;Villareal et al 2015). More recently, LDs accumulation increased in SARS-CoV2 patients, which act as fuel for SARS-CoV2 replication and consider as drug candidates to cure this pandemic virus (da Silva Gomes Dias et al 2020). LD also regulates intracellular bacteria-fighting machines and acts as a regulative role in innate immunity in mammalian cells (Bosch et al 2020).…”
Section: Introductionmentioning
confidence: 99%